Producing Ultra-High Strength Concrete using available conventional materials in Egypt - Bneni, Mohamed; Ahmad, Seleem; Gleim , Khalid; Mechail, Farah (Journal of Pure & Applied Sciences, 2024)
In this study, three trials were performed to obtain an Ultra-High Strength Concrete mix using widely available aggregates, mineral and chemical admixtures, then curing the specimens using a regular regime in clear water, also to observe the diversities of results of compressive strength test for both the cube and the cylinder shapes. For this purpose, three sizes of cubic molds having 70, 100, and 150 mm edge length and three sizes of cylindrical molds having dimensions (Ø 100mm x 150 mm), (Ø 100 mm x 200 mm) and (Ø 150mm x 300 mm) were used. The results of the compressive strength test as per ASTM C 39 showed a slight difference between 70 and 100 mm edge length cubes results. Whereas those of 150 mm cubes achieved a significantly higher result, the three sizes of the cylindrical shape have a minimal difference between the upper and lower results, not exceeding 9 %.